2007
DOI: 10.1128/mcb.00795-06
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of the Mod(mdg4)-67.2 BTB Domain Is Critical to Insulator Function in Drosophila melanogaster

Abstract: Enhancer-mediated promoter activation is a fundamental mechanism of gene regulation in eukaryotes (10, 44). Recently, sequences in different organisms have been identified that constrain enhancer action. These elements, known as insulators, block communication between an enhancer and promoter only when the insulator is positioned between these regulatory elements. Similarly, insulators prevent silencer interactions with promoters (6,10,30,44,45). The properties of insulators are exemplified by the gypsy insula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 48 publications
3
56
0
3
Order By: Relevance
“…Although analysis of the CP190 sequence suggests the presence of two SIMs, we have not observed a direct interaction between CP190 and SUMO in vitro. However, CP190 and Mod(mdg4)-67.2 contain several protein-protein interaction domains, including BTB/POZ Pai et al, 2004), that might be involved in direct interaction with many DNA-binding transcription factors, such as Su(Hw) and dCTCF, to facilitate their assembly into the insulator bodies (Gerasimova et al, 2007;Golovnin et al, 2007;Mohan et al, 2007;Pai et al, 2004). It is noteworthy that heat shock has proved to induce redistribution of CP190 to the nuclear periphery, in complex with SUMO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although analysis of the CP190 sequence suggests the presence of two SIMs, we have not observed a direct interaction between CP190 and SUMO in vitro. However, CP190 and Mod(mdg4)-67.2 contain several protein-protein interaction domains, including BTB/POZ Pai et al, 2004), that might be involved in direct interaction with many DNA-binding transcription factors, such as Su(Hw) and dCTCF, to facilitate their assembly into the insulator bodies (Gerasimova et al, 2007;Golovnin et al, 2007;Mohan et al, 2007;Pai et al, 2004). It is noteworthy that heat shock has proved to induce redistribution of CP190 to the nuclear periphery, in complex with SUMO.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown previously that Mod(mdg4)-67.2 facilitates Su(Hw) binding to insulator sequences (Gerasimova et al, 2000;Golovnin et al, 2007). The in vivo binding of the Su(Hw) and Mod(mdg4)-67.2 proteins to the gypsy and four endogenous Su(Hw) insulators (Parnell et al, 2006) was examined by ChIP analysis of chromatin isolated from the middle pupa stage (Fig.…”
Section: Cp190 Organizes Insulator Proteins Into Insulator Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both Cp190 and Mod(mdg4) have BTB/POZ domains, these domains differ in their amino acid sequences and their protein-protein interaction properties. Thus in vitro and in yeast two-hybrid assays, the BTB/POZ domains of Cp190 form homodimers (Bonchuk et al 2011;Vogelmann et al 2014) while the BTB/POZ domains of Mod(mdg4) form homo-and heterotypic multimers with the BTB/POZ domains of several other members of the tramtrack group (Golovnin et al 2007;Bonchuk et al 2011). Furthermore, the isolated BTB/POZ domains of Cp190 and Mod(mdg4) do not interact with each other (Bonchuk et al 2011).…”
mentioning
confidence: 99%
“…The molecular basis for interactions between individual insulators is not well understood but it has been suggested that Modifier of mdg4 [Mod(mdg4)] and CP190, both components of the insulator complex, might facilitate such interactions by mediating proteinprotein contacts between the BTB domains present in the two proteins (Gause et al 2001;Ghosh et al 2001;Golovnin et al 2007). These two properties of gypsy, sitespecific integration and insulator activity, have been the subject of intense but unrelated studies during the past two decades (Mevel-Ninio et al 1989;Bucheton 1995;Prud'homme et al 1995;Dej et al 1998;Gerasimova and Corces 2001;Labrador and Corces 2001;Capelson and Corces 2004).…”
mentioning
confidence: 99%